Evaluation of Garlic Extract in Extending Shelf Life of Paneer - Wanjari, Trupti P.; Badhe, Shekhar R.; Shukla, Vivek; Yadav , Satish R.; Vaidya, Vilas M. (International Journal of Livestock Research, 2019)
The present study was evaluated antimicrobial and antioxidant effect of different concentration of garlic extracts on shelf-life of paneer for storage period of 15 days under refrigeration condition (4oC±1). The antimicrobial activity of garlic extracts was evaluated against E. coli, S. aureus, P. aerugenosa using disc diffusion method and agar well diffusion method while its antioxidant property was evaluated based on its phenolic content (mg catecol equivalent/100 gm). The paneer cut into cubes were dipped in different concentrations of garlic extract (25%, 50% and 75% as T1, T2 and T3, respectively) and evaluated for antimicrobial and antioxidant properties against control sample. The samples were subjected to sensory evaluation when fresh and 5 days interval during 15 days storage periods. The sample were analysed for pH, TBARS, tyrosine and microbial analysis during storage. Paneer sample treated with 50% garlic extracts remained sound without changes its sensory qualities and microbiologically safe upto 10 days under refrigeration condition.